Simulation of moisture transport in fired-clay brick masonry structures accounting for interfacial phenomena. (15th January 2023) - Ramirez, R.; Ghiassi, B.; Pineda, P.; Lourenço, P.B.
Abstract: This paper presents a numerical study on moisture transport in brick masonry walls with a special focus on the simulation of their hygric performance as well as the hydraulic phenomena at the brick-mortar interface. A diffusivity model based on Fick's law is used to describe the moisture transport accounting for both liquid and water vapor movement. The necessary hygric parameters are obtained directly from experimental tests or determined by curve fitting. The proposed model is validated with respect to water absorption and drying tests. The good-fitness of the results is qualitatively assessed and an overall good agreement is found between the simulated and measured curves. It is demonstrated that the chosen liquid water diffusivity expression needs to be adjusted to represent drying processes; the necessary adjustment is made through a diffusivity factor implemented in the original analytical expression. The interface impact on water absorption is introduced as a hydraulic resistance. Moreover, it is hypothesized that the presence of successive interfaces entails an additive in-series effect. Conversely, the interfacial impact on drying is negligible. Finally, the proposed model is extended to different modeling approaches commonly used for mechanical studies of masonry. The necessary input data, modeling methodology, advantages and disadvantages associated with each modeling strategy are also discussed. The present study points out the need of studying water absorption in multi-layered structures made up of constituents with relatively similar hygric behavior. In such cases, the impact of imperfect contact at the interface between materials is not negligible. Highlights: Moisture transport simulations of absorption and drying phenomena in brick masonry. Validation against experimental data from single-material and multi-layered cases. The liquid diffusivity function needs to be adjusted to simulate drying cases. Brick-mortar imperfect contact modeled as an interface hydraulic resistance. Moisture transport model extended to commonly used modeling strategies for masonry.